La enseñanza musical en el Colegio Nacional de Sordomudos y Ciegos de España desde su fundación hasta la primera república: una aproximación documental - Burgos Bordonau, Esther (Revista General de Información y Documentación, 2004)
A documental study of the National School for the Deaf-Mute and Blind in Madrid as an example of an institution that, in addition to primary education and the teaching of trades, also offered musical education to its blind pupils.
Keywords: National School for the Deaf-Mute and Blind; Musical education